2006
DOI: 10.1093/jee/99.5.1691
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Bifenthrin (Onyx) and Carbaryl (Sevin SL) for Protecting Individual, High-Value Conifers from Bark Beetle Attack (Coleoptera: Curculionidae: Scolytinae) in the Western United States

Abstract: High-value trees, such as those located in residential, recreational, or administrative sites, are particularly susceptible to bark beetle (Coleoptera: Curculionidae: Scolytinae) attack as a result of increased amounts of stress associated with drought, soil compaction, mechanical injury, or vandalism. Tree losses in these unique environments generally have a substantial impact. The value of these individual trees, cost of removal, and loss of esthetics may justify protection until the main thrust of a bark be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
48
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(49 citation statements)
references
References 0 publications
1
48
0
Order By: Relevance
“…The experimental design used (Shea et al 1984) in these studies is regarded as a conservative test of efÞcacy and serves as a standard to determine the effectiveness of insecticide bole sprays (e.g., carbaryl, bifenthrin) for individual tree protection in the western United States (Fettig et al 2006). With bole sprays, bark beetles that land on target trees immediately contact the active ingredient before initiating host colonization.…”
Section: Effects Of Emamectin Benzoate (Eb) and Fipronil (Fip) Injementioning
confidence: 99%
See 1 more Smart Citation
“…The experimental design used (Shea et al 1984) in these studies is regarded as a conservative test of efÞcacy and serves as a standard to determine the effectiveness of insecticide bole sprays (e.g., carbaryl, bifenthrin) for individual tree protection in the western United States (Fettig et al 2006). With bole sprays, bark beetles that land on target trees immediately contact the active ingredient before initiating host colonization.…”
Section: Effects Of Emamectin Benzoate (Eb) and Fipronil (Fip) Injementioning
confidence: 99%
“…In 2003, bifenthrin (Onyx) was registered by the EPA for protection of ornamental trees against several Dendroctonus species, including southern pine beetle, but so far this product has not been widely available to consumers. Fettig et al (2006) indicated that the registered rate (0.06% [AI]) may be too low for efÞ-cacy against some western bark beetle species. Two other products, carbaryl (Sevin) and permethrin (Astro), are registered and effective against western bark beetle species, but they have proven ineffective against southeastern bark beetle species (Zhong et al 1994).…”
mentioning
confidence: 99%
“…Conversely, in our second study, none of the attractant + interruptant-treated trees was killed. Based on the results from the second study, the spruce trees were protected equivalent to a successful insecticide trial (Shea et al, 1984;Fettig et al, 2006).…”
Section: Verbenone and Conophthorin: Effects On Bark Beetle Colonizatmentioning
confidence: 99%
“…Cost may vary in warmer areas, where it may be necessary to use multiple applications/year to maintain adequate release rates of the interruptant during the flight period of the pest. The limited environmental impact of the treatment should be considered when evaluating and comparing costs with conventional insecticide treatments [$10.80 (Onyx) or $14.00 (Sevin SL)/tree; excluding labor (Fettig et al, 2006)]. …”
Section: Verbenone and Conophthorin: Effects On Bark Beetle Colonizatmentioning
confidence: 99%
See 1 more Smart Citation